Pengembangan Media Pembelajaran Mata Pelajaran Bahasa Inggris Melalui Running Teks Berbasis Media Proshow - Hayati, Ihda Lailatul; Suhono, Suhono (CV. Creative Tugu Pena, 2022)
This type of research used in this research is Research and Development (R&D). Research and development (R & D) is a research strategy or method that is quite effective in improving practice. The population in this study were all grade III students in MI Kutoanyar Kedu, Temanggung Regency, which amounted to 13 MI, but researchers only took samples from third grade students in MI Kutoanyar, amounting to 20 students. Development of learning media by proshow by running text on learning and understanding english language material by (a) Conducting preliminary research, (b) Conducting planning (defining abilities, formulating goals, determining material and sequence of learning, (c) Developing learning media with proshow , (d) Material expert test and media expert test, (e) Small-scale initial and revised field test, (f) Large-scale and final revision test, (g) application in learning. Based on the significance value of tcount = 5.709 with Sig. (2-tailed) 0,000. Before looking at the table of values of t, first must be with db = N - 2. Because the number of samples studied were 20 students, then db = 20-2 = 18. The value of db = 18 at a significance level of 5% obtained t-table = 1,345. Because tcount> ttable or 5.709> 1,345 and Sig. (2-tailed) = 0,000 <0.05 then H0 is rejected and H1 is accepted. So it can be concluded